A Study on the production system of Eastwind Garment Manufacturing Corporation - Almeida, Rose.; Asuncion, Roy.; Perdigon, Jun.; Reyes, Liza.; Rodriguez, Gerry; Rodriguez, Paul.; Tan, Simon (Diliman, Quezon City College of Engineering, 1983)
Eastwind Garment Manufacturing Company (EGMC) is basically a job-order type of production system. It manufactures mainly for export, specifically to the American and European markets. It faces tight competition from other manufacturers in Taiwan, Korea and Hong Kong. As such, Eastwind tries to put up an above average service level. In studying EGMC, the Group found out that it is falling short in achieving its objective. The very obvious manifestation of this is the delay in shipping finished products. This was traced from the different problem areas in, namely, inventory control, production scheduling, forecasting and the working conditions. In approaching the optimal solutions to these problems, the Eastwind Group (Group 5) came up with several alternative solutions?some of which are mathematical models. For forecasting, the most applicable method would be the Winter?s technique. This is so because of the seasonal characteristic of Eastwind?s annual demand. In production scheduling, the Group suggests that EGMC look into the possibility of applying SPT (Shortest Processing Time) rules, in sequencing the different production processes. This has, by far, provided the optimum value of whatever measure of performance is used in evaluating the system. To improve working conditions, the Group has suggested all three alternatives be considered. Cost estimates were done to help Eastwind determine the least cost alternative. It has to be stated that the above recommendations have their limitations. And these must be considered if the recommendations are to be useful to EGMC.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Eastwind Garment Manufacturing; Clothing trade; Production engineering